Human rights in education, science, and culture : legal developments and challenges - Donders, Yvonne; Volodin, Vladimir; Unesco (Aldershot, Hampshire, England ; New York, NY : Routledge ; UNESCO Publishing, 2016)
Human rights are at the heart of UNESCO's work in the fields of education, science and culture. Conceived from an international human rights legal framework, this publication combines insights into the content, scope of application and corresponding state obligations of these rights with analyses of issues relating to their implementation.--Publisher's description.
Interdependence and indivisibility of human rights / by Asbjørn Eide -- The justiciability of socio-economic rights : experience and problems / by Frans Viljoen -- The status of the development of indicators for economic, social, and cultural rights with particular emphasis to the rights to education, participation in cultural life, and access to the benefits of science / by Audrey R. Chapman -- The applicability of human rights between private parties / by Christian Courtis -- Content and scope of the right to education as a human right and obstacles to its realization / by Fons Coomans -- The legal framework of the right to take part in cultural life / by Yvonne Donders -- Study of the right to enjoy the benefits of scientific and technological progress and its application / by William A. Schabas.
Includes bibliographical references and index.
BIED
Keywords: Social rights; Right to education; Cultural policy; Economic policy; Human rights